2013
DOI: 10.5603/cj.2013.0030
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma concentrations of salicylic acid and high on ASA platelet reactivity in type 2 diabetes patients

Abstract: (OR 16.9, p = 0.006 and OR 5.34, p < 0.001, respectively). When using the VerifyNow Aspirin Assay, the concentrations of SA were significantly lower (p = 0.007) in the group with high on ASA platelet reactivity when compared with the group with normal on ASA platelet reactivity. In logistic regression analysis plasma SA concentration was found to be predictive of VerifyNow Aspirin Reaction Units (ARU) ≥ 550 (OR 3.86, p < 0.001 (Cardiol J 2013; 20, 2: 170-177)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…While ASA concentrations are more important for antiplatelet effects, in clinical studies SA levels are often measured because of the rapid breakdown of ASA to SA. However, SA levels have been shown to correlate with platelet function assays making it a useful surrogate measure [ 12 ]. In this study, ASA concentrations over 1,000 ng/mL were achieved within 5 minutes with the soluble formulation in both the fasting and fed states, however, this level was not achieved with the chewed tablet until 7 minutes in the fasting state, and was further delayed (10 minutes) in the fed state.…”
Section: Discussionmentioning
confidence: 99%
“…While ASA concentrations are more important for antiplatelet effects, in clinical studies SA levels are often measured because of the rapid breakdown of ASA to SA. However, SA levels have been shown to correlate with platelet function assays making it a useful surrogate measure [ 12 ]. In this study, ASA concentrations over 1,000 ng/mL were achieved within 5 minutes with the soluble formulation in both the fasting and fed states, however, this level was not achieved with the chewed tablet until 7 minutes in the fasting state, and was further delayed (10 minutes) in the fed state.…”
Section: Discussionmentioning
confidence: 99%
“…Different letters given in the upper index indicate the occurrence of statistical differences in the values of a given parameter between the three groups (Kruskal-Wallis ANOVA, p < 0.05); CRP -C-reactive protein; GFR -glomerular filtration rate; HDL-C -high density lipoprotein cholesterol; LDL-C -low density lipoprotein cholesterol Beata Krasińska et al, The effect of ASA dosed at bedtime on the anti-aggregation effect It should be remembered that physiologically, at all the times, new and uninhibited plates are released into the blood, which constitute about 10% of the total number. The release of new platelets may be greater in people with vascular disease [34][35][36]. It has been shown that in up to 25% of patients, inhibition of platelets by ASA decreases gradually within 24 h after its administration [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al (2012) reported that salicylic acid pharmacokinetic study in diabetic rats achieved lower blood concentrations of salicylic acid than normal rats with a higher apparent clearance (CL/F) possibly due to incomplete (47%) bioavailability. Salicylic acid pharmacokinetic mechanisms might contribute to lower plasma salicylic acid levels, and subsequently incomplete inhibition of thromboxane A 2 synthesis as measured with S-TxB 2 concentrations and increased platelet reactivity in DM patients (Postula et al, 2013).…”
Section: Salicylic Acidmentioning
confidence: 99%